Essay on Senior Seminar and Syllabus Example - Pike, Diane (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this seminar, students will:• Review, reflect upon, and articulate synthesis and evaluation of the discipline of sociology, as a whole.• Assess and evaluate the value and meaning of sociology in understanding the world today.• Meet the specific outcomes of a keystone course in the AugCore Curriculum as a way to develop and present vocational and professional identity as a sociology major; intentionally, reflect upon and connect general education with the major as preparation for life as an effective, informed, and ethical citizen.• Department Student Learning Outcomes for 300/400 level sociology courses:1. Students are able to recognize and analyze the interconnectedness of substantive course knowledge at the appropriate level of analysis--macro, meso, and micro sociological.2. Students are able to identify research sources as qualitative and quantitative and to assess their relative contributions to questions and problems.3. Students are able to analyze, apply, and evaluate a course-relevant sociological theory to a course based question or problem.4. Students can articulate the critical thinking framework used in the course and demonstrate its application in multiple assignments or activities.5. Students demonstrate competency in writing or speaking skill at an upper division level through substantial course assignments.